Dental hygienist job autonomy depends on the period of dental hygiene education - Young-Eun Jang; Nam-Hee Kim (Wolters Kluwer Medknow Publications, 2020)
Context: Independent dental hygiene practice is critical in regions with low accessibility to dental services, as well as for preventing and managing oral diseases among children and the elderly from low-income families, as these individuals are highly vulnerable to oral diseases. Aims: We investigated whether the job autonomy of dental hygienists has been maintained, in accordance with the guidelines of the International Federation of Dental Hygienists (IFDH). Settings and Design: This study comprised a cross-sectional literature review. Subjects and Methods: We reviewed national reports and articles published in 23 countries selected for analysis to determine the degree of dental hygienist job autonomy, based on the extent of dental hygiene education. We divided the countries into two groups, based on the historical length of dental hygienist education. Statistical Analysis Used: We classified education as direct access, indirect supervision, and direct supervision. Two researchers reviewed and revised the classification results to ensure reliability. The Kappa value was 0.96 points. Statistical analysis was performed by PASW statistics 23.0 program (SPSS Inc., Chicago, IL, USA.). Results: Countries with >40 years of educating dental hygienists exhibited more independent dental hygienist practices than those with less than 40 years of educating dental hygienists. Conclusions: Countries with >40 years of experience in educating dental hygienists largely guarantee independent dental hygiene practice for dental hygienists, in accordance with IFDH guidelines. The society's need for dental hygienists is fulfilled and professional competency is maintained in these contexts; thus, it should be required for dental hygienists to maintain independent dental hygiene practices.